Enhancing high-potential stability of Ni-rich LiNi0.8Co0.1Mn0.1O2 cathode with PrF3 coating. Issue 5 (1st March 2021) - Li, Jiawei; Wang, Jingjing; Lu, Xianghao; Jiang, Hongyu; Zhang, Quanhai; Wang, Bin; Lai, Chunyan
Abstract: It is still a huge challenge to improve the safety and stability of Ni-rich (LiNi0.8 Co0.1 Mn0.1 O2 ) cathode materials at elevated potential. Herein, the PrF3 layer is employed to protect LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) via a simple wet chemical process. It was confirmed by XRD, HR-SEM, TEM, EDS, and XPS tests that PrF3 is evenly covered throughout the surface of NCM811 without affecting the particle size and surface morphology. In particular, 1 wt% PrF3 coated NCM811 exhibits excellent stability and rate capability with the capacity retention of 86.3% after 100 cycles at 1 C under a cut-off potential of 4.3 V, while the retention of pristine one is only 73.8%. Moreover, the capacity retention of 1 wt% PrF3 coated samples enhances from 74.5% to 88.5% after 50 cycles at 1 C under higher cut-off voltage of 4.6 V. The superior performance for coated samples can be attributed to the fact that PrF3 can effectively isolate the active material and the electrolyte from HF corrosion, and at the same time, reduce the generation of micro-cracks on the surface during prolonged cycles. Furthermore, as a physical barrier, PrF3 alleviates the dissolution of transition metals in the electrolyte largely. These results suggest that the stability of NCM811 can be greatly upgraded at high voltage by PrF3 coating. Graphical abstract: A schematic image of the electrode material during the cycle and electrochemical performance. Image 1 Highlights: 1 wt% PrF3 coated NCM811 delivered superior electrochemical characteristic at cut-off potential of 4.3 and 4.6 V. The PrF3 protects the cathode material from the corrosion of the electrolyte. The PrF3 coated NCM811 suppressed microcracks and diminished the dissolution of transition metals during long cycles.